Design, Synthesis, and Biological Evaluation of Novel Simvastatin Derivatives with Potent Lipid-Lowering Effects and HMG-CoA Reductase Inhibition in Hyperlipidemic Rats - Sheaa, Amaal Hussein; Abass, Abass Fadhil; Zearah, Sameera Ahmed (Indonesian Journal of Chemistry, 2026)
In this study, two novel ester derivatives of simvastatin were synthesized via a convenient one-pot esterification method using acetic acid and propanoic acid. The synthesized compounds were fully characterized by FTIR, 1H-NMR, 13C-NMR, and mass spectrometry. Their safety profiles were evaluated through acute toxicity (LD50) and cytotoxicity tests, affirming their biocompatibility. To assess their hypolipidemic potential, both derivatives (A1 and A2) were administered to a cholesterol-induced hyperlipidemic rat model. Lipid profiles, including total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), and very low-density lipoprotein (VLDL), were measured post-treatment. The results revealed that both compounds significantly improved lipid parameters, with the propanoate derivative (A2) exhibiting the most potent lipid-lowering activity, surpassing even the reference drug, simvastatin. Furthermore, biochemical assays demonstrated a substantial reduction in hepatic HMG-CoA reductase activity, particularly in the A4-treated group, suggesting a direct inhibitory effect on cholesterol biosynthesis. These findings suggest that the synthesized derivatives may serve as promising candidates for the development of safer and more effective lipid-lowering agents.